Challenges Encountered During the Veterinary Disaster Response: An Example from Chile - Garde, Elena (Animals (Basel), 2013)
SIMPLE SUMMARY: Disaster preparedness for companion animals has economic, social and welfare benefits, yet many countries continue to omit dogs and cats from their national and regional contingency planning. Responses therefore, are often chaotic, inefficient and uncoordinated, or absent altogether. Documented experiences in Chile contribute to the information supporting the inclusion of companion animals into locally relevant disaster plans. These plans serve to prepare communities and authorities, identify resources available, establish a chain of command, develop local priorities, and subsequently reduce the negative impacts on both human and animal communities. ABSTRACT: Large-scale disasters have immeasurable effects on human and animal communities. Evaluating and reporting on the response successes and difficulties encountered serves to improve existing preparedness documents and provide support to those in the process of developing plans. Although the majority of disasters occur in low and middle income nations, less than 1% of the disaster literature originates from these countries. This report describes a response to a disease outbreak in domestic dogs in Dichato, Chile following the 2010 earthquake/tsunami. With no national plan coordinating the companion animal response, there was a chaotic approach among animal welfare organizations towards rescue, diagnosis, treatment and record-keeping. Similar to the medical response following the 1985 earthquake near Santiago, we experienced problems within our own teams in maintenance of data integrity and protocol compliance. Loss of infrastructure added complications with transportation, communications and acquisition of supplies. Similar challenges likely occur in most disasters, but can be reduced through pro-active planning at national and local levels. There is sufficient information to support the human and animal welfare benefits of including companion animals in national planning, and lessons learned through this and other experiences can assist planners in the development of comprehensive and locally relevant contingency plans.